Pengaruh Kematerialitasan Kecurangan dan Tingkat Retaliation Terhadap Intensi Auditor Internal Dalam Melakukan Whistleblowing - Ester Putri Gita Pratiwi; Bernadetta Diana (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
Regardless the level of organization position, fraud cases can be occurred both internationally or Indonesia itself that made the instrument to detect fraudulence necessary. Thus, the oversight and the predominant duty is necessary in every organization. That duty should be done by the Corporate Internal auditor because he/ she can perform assurance and controlling services to the organization, according to the COSO standard. Nonetheless, even internal auditor were mandate to be independent, they still the part of the company that made an ethical dilemma for them to ‘blow the whistle’ or to keep it silent. The aim of this research is to give the empirical information about the influence of fraudulence materiality level, retaliation level on internal auditor whistleblowing intention Internal auditor whistleblowing intention can be influenced by the fraudulence materiality level and the retaliation level. This research is a quasi experimental research with 2x2 between subject experimental design. Accounting student from Widya Mandala Catholic University of Surabaya was the subject of this research with the criteria those who have passed internal auditing subject. Scenarios made accordance with the circumstances that occur within the company become the instrument of this research. Fraudulence materiality level was proven has an influence on internal auditor whistleblowing intention as the final results. But, retaliation level was failed to influence internal auditor whistleblowing intention signifficantly.